2009
DOI: 10.1128/ec.00270-08
|View full text |Cite
|
Sign up to set email alerts
|

AgtA, the Dicarboxylic Amino Acid Transporter of Aspergillus nidulans , Is Concertedly Down-Regulated by Exquisite Sensitivity to Nitrogen Metabolite Repression and Ammonium-Elicited Endocytosis

Abstract: We identified agtA, a gene that encodes the specific dicarboxylic amino acid transporter of Aspergillus nidulans. The deletion of the gene resulted in loss of utilization of aspartate as a nitrogen source and of aspartate uptake, while not completely abolishing glutamate utilization. Kinetic constants showed that AgtA is a high-affinity dicarboxylic amino acid transporter and are in agreement with those determined for a cognate transporter activity identified previously. The gene is extremely sensitive to nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 75 publications
(89 reference statements)
3
64
0
Order By: Relevance
“…However, the data presented in this article imply that if they play a role in endocytosis in A. nidulans, this role is minor or limited to specific cargos, which remain unidentified. Neither the endocytosis of FM4-64 nor the ammonium-elicited endocytosis of the AgtA (dicarboxylic amino acid transporter [5]; data not shown) or PrnB (the major proline transporter [41]; data not shown) are visibly affected in mycelia by a deletion of pilA, encoding the only eisosomal protein present in discrete foci in hyphae. It should be noted that although the AgtA and PrnB proteins of A. nidulans and the Hxt2 protein of S. cerevisiae are transporters with a homogeneous distribution in the plasma membrane, upon endocytosis Hxt2 accumulates in discrete plasma membrane-associated foci (52), while the two A. nidulans proteins do not (5).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, the data presented in this article imply that if they play a role in endocytosis in A. nidulans, this role is minor or limited to specific cargos, which remain unidentified. Neither the endocytosis of FM4-64 nor the ammonium-elicited endocytosis of the AgtA (dicarboxylic amino acid transporter [5]; data not shown) or PrnB (the major proline transporter [41]; data not shown) are visibly affected in mycelia by a deletion of pilA, encoding the only eisosomal protein present in discrete foci in hyphae. It should be noted that although the AgtA and PrnB proteins of A. nidulans and the Hxt2 protein of S. cerevisiae are transporters with a homogeneous distribution in the plasma membrane, upon endocytosis Hxt2 accumulates in discrete plasma membrane-associated foci (52), while the two A. nidulans proteins do not (5).…”
Section: Discussionmentioning
confidence: 95%
“…nidulans is arguably, among the Pezizomycotina, the organism where membrane proteins and endocytosis have been better studied. In this organism, a number of transporters driven by their physiological promoters have been visualized in the cell membrane (UapC [48], PrnB [45], UapA and AzgA [35], AgtA [5], MstE [14], FcyB [51], UreA [M. Sanguinetti and A. Ramón, personal communication], and FurD [G. Diallinas and F. Borbolis, personal communication]). Load-and-chase experiments have shown that when the dye FM4-64 is endocytosed, it first appears in cortical punctate structures (36).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous YAT transporters can be identified in all sequenced genomes of fungi. Characterized members include 15 of the 16 characterized amino acid transporters of Saccharomyces cerevisiae (5,6), two proteins of Aspergillus nidulans, PrnB and AgtA (7,8), as well as transporters from Candida glabrata, Neurospora crassa, and Penicillium chrysogenum (9 -11). These proteins display different specificities and are subject to tight transcriptional and post-translational regulation (12)(13)(14).…”
mentioning
confidence: 99%